СТАТЬ І ВИКОНАННЯ МАТЕРИНСЬКОЇ ФУНКЦІЇ ЯК ПІДСТАВИ ДИФЕРЕНЦІАЦІЇ ПРАВОВОГО РЕГУЛЮВАННЯ ВИНИКНЕННЯ ТРУДОВИХ ПРАВОВІДНОСИН ІЗ ЖІНКАМИ — КАНДИДАТАМИ НА СЛУЖБУ ДО ОРГАНІВ ВНУТРІШНІХ СПРАВ УКРАЇНИ - Shulzhenko, I.V. (Економіка та право, 2010)
The article analyzes the expediency of differentiating the legal regulation of origin of labour legal relations with women — candidates to the service in the internal security organs (ІSO) of Ukraine and offers proposals on removing legal collisions arising as a result of the above differentiation. The author comes to the conclusion that the consequences of differentiation of the legal regulation of origin of labour legal relations with women — candidates to the service in ISO of Ukraine are either additional legal guarantees provided for women as privileges and advantages or limitations or prohibitions.